Philosophical Justifications For The Restoration Of Independent Statehood Of Zakaryans - Petrosyants, Tigran (Զանգակ հրատ.)
the middle of the 80s of the 12 th -century revivals in the consciousness of the Armenians in aspiration for independence, the formation of new noble families, the formation of a powerful army, the absolute unity of new nobility, the stubborn preservation of their faith, the legislative formation of the judicial system, the final formation of the tools of the network marriage institution ensured the creation and half- century existence of an independent statehood of Armenia in 1185-1236.
Keywords: Philosophy of education